Haplotypic Distribution of SARS-CoV-2 Variants in Cases of Intradomiciliary Infection in the State of Rondônia, Western Amazon - Karolaine Santos Teixeira; Márlon Grégori Flores Custódio; Gabriella Sgorlon; Tárcio Peixoto Roca; Jackson Alves da Silva Queiroz; Ana Maisa Passos-Silva; Jessiane Ribeiro; Deusilene Vieira (Bioinformatics and Biology Insights)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has a high transmissibility profile which favors the accumulation of mutations along its genome, providing the emergence of new variants. In this context, haplotype studies have allowed mapping specific regions and combining approaches and tracking phylogenetic changes. During the COVID-19 pandemic, it was notorious that home environments favored the circulation of SARS-CoV-2, in this study we evaluated 1,407 individuals positive for SARS-CoV-2, in which we located 53 families in the period from June 2021 to February 2023. The epidemiological data were collected in E-SUS notifica and SIVEP-gripe. Then, the genetic material was extracted using the commercial kit and the viral load was evaluated and the viral genomes were sequenced using the Illumina MiSeq methodology. In addition, the circulation of 3 variants and their respective subvariants was detected. The delta variant represented the highest number of cases with 45%, the Omicron variant 43% and the lowest number with 11% of cases the Gamma variants. There were cases of families infected by different subvariants, thus showing different sources of infection. The haplotype network showed a distribution divided into 6 large clusters that were established according to the genetic characteristics observed by the algorithm and 224 Parsimony informative sites were found. In addition, 92% of subjects were symptomatic and 8% asymptomatic. The secondary attack rate of this study was 8.32%. Therefore, we can infer that the home environment favors the spread of SARS-CoV-2, so it is of paramount importance to carry out genomic surveillance in specific groups such as intradomiciliary ones.